Determining the antioxidant activity of certain medicinal plants of Attapady, (Palakkad), India using DPPH assay - M.Karpagavalli, K.R. Sini, B. N. Sinha (Current Botany, 2011)
<span style="font-family: Byington; font-size: 8pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Cellular damage or oxidative injury arising from free radicals or reactive oxygen species (ROS) now appears the fundamental mechanism underlying a number of human neurodegenerative disorders, diabetes, inflammation, viral infections, autoimmune pathologies and digestive system disorders. Free radicals are generated through normal metabolism of drugs, environmental chemicals and other xenobiotics as well as endogenous chemicals, especially stress hormones (adrenalin and noradrenalin). Accumulated evidence suggests that ROS can be scavenged through chemoprevention utilizing natural antioxidant compounds present in foods and medicinal plants. India is blessed with enormous biodiversity resources, but plagued with several diseases, including those with ROS as the etiological factor. In this study the antioxidant activity and radical scavenging activity of methanolic extracts of selected plant materials, traditionally used by the tribes of Attapady regions as folk remedies was evaluated against 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical. Cassia occidentalis, Clitoria ternatea, Trianthema decandra, Capparis zeylanica, Anisomeles malabarica and Plumbago zeylanica exhibited strong antioxidant activity as compared to other plants. Trianthema decandra showed the highest antioxidant activity. The present study reveals that these plants are of therapeutic potential due to their high free-radical scavenging activity.